Italy and the global imperialist struggle between 1940-2000 AD (Damascus University Journal of Historical Studies, 2024)
The research studies the European reality (especially the West) politically, economically and militarily, in order to find out the importance of the Italian role in the midst of the European competition at the international level over the escalating. Which led to two world wars, the most important of which was the Second World War 1939-1945 AD, which in turn constituted a major turning point in international changes, as countries disappeared and others rose, as this coincided with the emergence of two prominent camps at the international level with two different ideologies, which led the outbreak of a cold war that did not stop Except at the expense of one of them or the dissolution of one of the parties.In this context, the objectives of the research lie in studying the most prominent stages that Italy went through until it reached the stage of union with the rest the European countries, and not to get involved in the military and political conflict between the two prominent poles at the time, namely the Soviet Union and the United states AmericaThe method used in this research is the inductive method for the most prominent sources and references. Which studies the European reality in general, politically and economically, and its most important results are represented in embodying the Italian reality in particular, and proving the existence of European power and not allowing any force to interfere with them politically and economically in a way that increases their political division and economic weakness, and they succeeded in this field, as will be shown during the research.
Keywords: Fascism; War; Imperialism; Communism; Capitalism; Socialism; Union